Wide local resection of sacral chordoma through posterior midline approach - Islam, Md. Anowarul; Mishra, Dipendra; Batajoo, Santosh; Shrestha, Manish (Bangabandhu Sheikh Mujib Medical University Journal, 2018)
This study was performed in 21 patients with sacral chordoma from July 2008 to June 2017 and posterior surgical approach was used for resection. Out of 21 patients, 12 had done subtotal sacrectomy and the remaining 9 had done partial sacrectomy. Their follow-up periods were at least five years. Operative time ranged between two to four hours. All patients recovered well from operation and two to five units of blood transfusion were needed for each. After operation, majority of the patients developed some bowel and bladder dysfunction and five patients developed wound infection. During the follow-up, two patients had tumor recurrence and one patient expired two years after operation. The remaining 18 patients were tumor-free at the 5-years follow-up. Wide surgical resection via the posterior midline approach could be a good management plan for the sacral chordoma. However, complete removal with surgical margin varies according to the location of the tumor.